Integrative motivation and global language (English) acquisition in Poland - Gardner, Robert C. (Zakład Filologii Angielskiej Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2012)
This study investigated the consistency of a measure of integrative motivation in the prediction of achievement in English as a foreign language in 18 samples of Polish school students. The results are shown to have implications for concerns expressed that integrative motivation might not be appropriate to the acquisition of English because it is a global language and moreover that other factors such as the gender of the student or the environment of the class might also influence its predictability. Results of a hierarchical linear modeling analysis indicated that for the older samples, integrative motivation was a consistent predictor of grades in English, unaffected by either the gender of the student or class environment acting as covariates. Comparable results were obtained for the younger samples except that student gender also contributed to the prediction of grades in English. Examination of the correlations of the elements of the integrative motivation score with English grades demonstrated that the aggregate score is the more consistent correlate from sample to sample than the elements themselves. Such results lead to the hypothesis that integrative motivation is a multi-dimensional construct and different aspects of the motivational complex come into play for each individual. That is, two individuals can hold the same level of integrative motivation and thus attain the same level of achievement but one might be higher in some elements and lower in others than another individual, resulting in consistent correlations of the aggregate but less so for the elements.
Keywords: socio-educational model of second language acquisition; integrative motivation; integrativeness; attitudes toward the learning situation; language anxiety